Resin composition, resin film, resin-coated metal foil, prepreg, metal-clad laminate, and printed wiring board

A resin composition with a balanced mix of anhydrous magnesium carbonate and alumina fillers addresses moldability issues, enhancing thermal conductivity and heat resistance while preventing defects in insulating layers.

JP7603262B2Active Publication Date: 2024-12-20PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021553486
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-25
Filing Date
2020-10-21
Publication Date
2024-12-20
Estimated Expiration
2040-10-21

AI Technical Summary

Technical Problem

Existing resin compositions containing inorganic fillers face challenges in achieving optimal moldability, as they either lack sufficient fluidity to fill gaps between conductive wiring or exhibit excessive flow during molding, leading to defects in insulating layers.

Method used

A resin composition comprising a thermosetting resin and inorganic fillers, including a first filler with anhydrous magnesium carbonate and alumina, and a nano-sized second filler, balanced at specific volume ratios to enhance thermal conductivity, heat resistance, and moldability, while preventing excessive flow.

Benefits of technology

The composition achieves improved moldability, ensuring gaps between conductive wirings are filled without excessive flow, maintaining high thermal conductivity and heat resistance, and reducing drill wear during processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603262000005
    Figure 0007603262000005
  • Figure 0007603262000006
    Figure 0007603262000006
  • Figure 0007603262000007
    Figure 0007603262000007
Patent Text Reader

Abstract

This disclosure provides a resin composition containing an inorganic filler and having excellent moldability. The resin composition contains a thermosetting resin (A) and an inorganic filler (B). The inorganic filler (B) contains a first filler (B1) and a nano-size second filler (B2) with a smaller particle diameter than the first filler (B1). The first filler (B1) contains an anhydrous magnesium carbonate filler (b1) and an alumina filler (b2). The proportion of the first filler (B1) in relation to the total solid quantity of the resin composition is 50-90 vol% and the proportion of the second filler (B2) is 0.1-2.0 vol%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a resin composition, a resin film, a metal foil with resin, a prepreg, a metal-clad laminate, and a printed wiring board, and more particularly to a resin composition containing a thermosetting resin, a resin film made from the resin composition, a metal foil with resin made from the resin composition, a prepreg made from the resin composition, a metal-clad laminate made from the resin composition, and a printed wiring board made from the resin composition. [Background technology]

[0002] Patent Document 1 discloses a thermally conductive resin composition. This thermally conductive resin composition contains two or more kinds of inorganic fillers in a total amount of 60 to 95 mass %. The first inorganic filler has a Mohs hardness of 4 or more, and the second inorganic filler has a Mohs hardness of 3 or less. Furthermore, the ratio of the first inorganic filler to the second inorganic filler is 1:1 to 0.01. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-087250 A Summary of the Invention

[0004] An object of the present disclosure is to provide a resin composition having excellent moldability, a resin film made from the resin composition, a resin-coated metal foil made from the resin composition, a prepreg made from the resin composition, a metal-clad laminate made from the resin composition, and a printed wiring board made from the resin composition.

[0005] A resin composition according to an embodiment of the present disclosure contains a thermosetting resin (A) and an inorganic filler (B). The inorganic filler (B) contains a first filler (B1) and a nano-sized second filler (B2) having a smaller particle size than the first filler (B1). The first filler (B1) contains anhydrous magnesium carbonate filler (b1) and an alumina filler (b2). The proportion of the first filler (B1) to the total solid content in the resin composition is 50% by volume or more and 90% by volume or less, and the proportion of the second filler (B2) is 0.1% by volume or more and 2.0% by volume or less.

[0006] A resin film according to one embodiment of the present disclosure contains the resin composition, a dried product of the resin composition, or a semi-cured product of the resin composition.

[0007] A resin-coated metal foil according to one embodiment of the present disclosure comprises a resin layer containing the resin composition, a dried product of the resin composition, or a semi-cured product of the resin composition, and a metal foil overlying the resin layer.

[0008] A prepreg according to one embodiment of the present disclosure includes a substrate, and the substrate is impregnated with the resin composition, a dried product of the resin composition, or a semi-cured product of the resin composition.

[0009] A metal-clad laminate according to one embodiment of the present disclosure includes an insulating layer containing a cured product of the resin composition, and a metal foil overlying the insulating layer.

[0010] A printed wiring board according to one embodiment of the present disclosure includes an insulating layer containing a cured product of the resin composition, and a conductor layer overlying the insulating layer. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view of a resin film according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a resin-coated metal foil according to an embodiment of the present disclosure. [Diagram 3]FIG. 3 is a schematic cross-sectional view of a prepreg according to one embodiment of the present disclosure. [Figure 4] FIG. 4 is a schematic cross-sectional view of a metal-clad laminate according to one embodiment of the present disclosure. [Diagram 5] 5A and 5B are schematic cross-sectional views of a printed wiring board according to an embodiment of the present disclosure, and a multi-layer printed wiring board according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In resin compositions for producing resin films, resin-attached metal foils, prepregs, metal-clad laminates, printed wiring boards, etc., inorganic fillers are used to improve performance such as thermal conductivity and heat resistance, but inorganic fillers tend to cause a decrease in moldability. In particular, when a resin composition containing an inorganic filler is molded to produce an insulating layer and conductor wiring is embedded in the insulating layer, it is preferable that the resin composition has good fluidity during molding so that the insulating layer is sufficiently filled in the gaps of the conductor wiring. On the other hand, in order to prevent the resin composition from flowing out excessively during molding, it is preferable that the resin composition does not have excessive fluidity. In order to impart appropriate fluidity to such a resin composition, for example, the amount of inorganic filler is adjusted, but it is difficult to impart appropriate fluidity to the resin composition by that alone.

[0013] Therefore, the inventors have conducted research to develop a resin composition that contains an inorganic filler and has excellent moldability, and as a result, have completed the present disclosure.

[0014] Hereinafter, one embodiment of the present disclosure will be described.

[0015] The resin composition according to the present embodiment contains a thermosetting resin (A) and an inorganic filler (B). The inorganic filler (B) contains a first filler (B1) and a nano-sized second filler (B2) having a particle size smaller than that of the first filler (B1). The first filler (B1) contains anhydrous magnesium carbonate filler (b1) and an alumina filler (b2). The ratio of the first filler (B1) to the total solid content in the resin composition is 50% by volume or more and 90% by volume or less, and the ratio of the second filler (B2) is 0.1% by volume or more and 2.0% by volume or less. The solid content refers to the components in the resin composition excluding volatile components (components that do not remain in the cured product) such as solvents.

[0016] A resin film can be produced from the resin composition. A resin-coated metal foil can also be produced from the resin composition. A prepreg can also be produced from the resin composition. A metal-clad laminate and a printed wiring board can also be produced from each of the resin film, the resin-coated metal foil, and the prepreg.

[0017] According to this embodiment, the alumina filler (b2) has particularly high heat resistance, and therefore the cured product of the resin composition can have high heat resistance. In addition, the anhydrous magnesium carbonate filler (b1) has good heat resistance because it does not have crystallization water, and therefore is less likely to inhibit the heat resistance of the cured product. Furthermore, the hardness of the anhydrous magnesium carbonate filler (b1) is lower than that of the alumina filler (b2). Therefore, the anhydrous magnesium carbonate filler (b1) can make it difficult for the drill to be worn when the cured product of the resin composition is processed with a drill. Therefore, the cured product of the resin composition is likely to have high heat resistance and drill processability.

[0018] Furthermore, the resin composition can have a suitable fluidity during molding due to the second filler (B2). This makes it easier for the insulating layer to be sufficiently filled into the gaps between the conductor wirings, particularly when the resin composition is molded to prepare an insulating layer and the conductor wiring is embedded in the insulating layer. Furthermore, excessive flow of the resin composition during molding is suppressed, and for example, the resin composition is less likely to flow out of the insulating layer, making it less likely that molding defects will occur in the insulating layer.

[0019] As a result, in this embodiment, a resin composition containing an inorganic filler and having excellent moldability can be obtained.

[0020] This embodiment will now be described in more detail.

[0021] The components of the resin composition will be described.

[0022] The thermosetting resin (A) includes, for example, at least one of a monomer and a prepolymer. The prepolymer may include an oligomer. The type of polymerization reaction of the thermosetting resin (A) is not particularly limited. Specific examples of the polymerization reaction include chain polymerization and step-growth polymerization. A representative example of chain polymerization is radical polymerization. A representative example of step-growth polymerization is polyaddition.

[0023] The thermosetting resin (A) contains at least one selected from the group consisting of, for example, an epoxy resin (a), a phenoxy resin, a polyimide resin, a polyester resin, a triazine resin, a maleimide resin, a polyphenylene ether resin, and a polyphenylene ether resin having a functional group containing a C-C unsaturated bond in one molecule, and derivatives of these resins.

[0024] Preferably, the thermosetting resin (A) contains at least one of an epoxy resin (a) and a phenoxy resin. The epoxy resin (a) preferably contains a resin having two or more epoxy rings (oxirane rings) in one molecule. The epoxy resin (a) may be liquid or solid.

[0025] The epoxy resin (a) contains at least one selected from the group consisting of, for example, bisphenol-type epoxy resins, novolac-type epoxy resins, aryl alkylene-type epoxy resins, naphthalene skeleton-modified epoxy resins, trifunctional epoxy resins, phenoxy resins, triphenylmethane-type epoxy resins, anthracene-type epoxy resins, dicyclopentadiene-type epoxy resins, norbornene-type epoxy resins, fluorene-type epoxy resins, flame-retardant epoxy resins obtained by halogenating any of the above epoxy resins, epoxy resins modified with a phosphorus compound, pre-reaction products of epoxy resins and polyphenylene ether resins, and pre-reaction products of epoxy resins and acid anhydrides, as well as derivatives of these resins.

[0026] The bisphenol type epoxy resin contains at least one selected from the group consisting of, for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, and derivatives of these resins.

[0027] The novolac type epoxy resin contains at least one selected from the group consisting of, for example, phenol novolac type epoxy resin, cresol novolac type epoxy resin, and derivatives of these resins.

[0028] The aryl alkylene type epoxy resin contains at least one selected from the group consisting of, for example, biphenyl type epoxy resins, xylylene type epoxy resins, phenol aralkyl type epoxy resins, biphenyl aralkyl type epoxy resins, biphenyl novolac type epoxy resins, biphenyl dimethylene type epoxy resins, trisphenol methane novolac type epoxy resins, tetramethyl biphenyl type epoxy resins, and derivatives of these resins.

[0029] The naphthalene skeleton-modified epoxy resin contains at least one selected from the group consisting of, for example, naphthalene type epoxy resins, naphthalene skeleton-modified cresol novolac type epoxy resins, naphthalene diol aralkyl type epoxy resins, naphthol aralkyl type epoxy resins, methoxynaphthalene modified cresol novolac type epoxy resins, methoxynaphthalene dimethylene type epoxy resins, and derivatives of these resins.

[0030] Phenoxy resin is a resin made by polymerizing bisphenol A type epoxy resin into a linear chain.

[0031] The thermosetting resin (A) preferably contains a liquid resin (for example, an epoxy resin that is liquid at room temperature).

[0032] When the thermosetting resin (A) contains an epoxy resin (a), the epoxy resin (a) preferably contains an epoxy resin (a1) having a softening point of 75° C. or less. The proportion of the epoxy resin (a1) is preferably 30% by mass or more relative to the epoxy resin (a). In this case, when a sheet-like member (sheet material) such as a resin film or prepreg is produced from the resin composition, the sheet material is likely to have good flexibility, and is less likely to break even when the sheet material is bent. The proportion of the epoxy resin (a1) is preferably 30% by mass or more, and more preferably 50% by mass or more. The proportion of the epoxy resin (a1) may be 100% by mass. The softening point of the epoxy resin (a1) is more preferably 70° C. or less, and more preferably 65° C. or less. The softening point can be measured by the ring and ball method using a softening point tester in accordance with JISK 7231 (General rules for testing epoxy resins and curing agents).

[0033] When the thermosetting resin (A) contains at least one of the epoxy resin (a) and the phenoxy resin, the resin composition preferably further contains a curing agent. The curing agent contains at least one selected from the group consisting of, for example, dicyandiamide, a phenolic resin, an acid anhydride, and a cyanate ester. The curing agent preferably contains, in particular, dicyandiamide. In that case, the resin film 1 is likely to have good flexibility. The phenolic resin may contain a phosphorus-containing phenolic resin. In this case, the flame retardancy of the resin composition can be improved.

[0034] The resin composition may further contain a catalyst. The catalyst can promote the reaction between the thermosetting resin (A) and the curing agent. The catalyst contains at least one selected from the group consisting of, for example, metal salts of organic acids (metal soaps, etc.), tertiary amines, and imidazoles. The metal salts of organic acids contain at least one selected from the group consisting of metal salts of organic acids such as octanoic acid, stearic acid, acetylacetonate, naphthenic acid, salicylic acid, and octylic acid, such as Zn, Cu, and Fe. An example of a metal salt of an organic acid is zinc octylate (zinc bis(2-ethylhexanoate)). The tertiary amine contains at least one selected from the group consisting of, for example, triethylamine, triethanolamine, and the like. The imidazole contains at least one selected from the group consisting of, for example, 2-ethyl-4-methylimidazole, 4-methylimidazole, and the like.

[0035] As described above, the resin composition contains an inorganic filler (B), and the inorganic filler (B) contains a first filler (B1) and a nano-sized second filler (B2) having a smaller particle size than the first filler (B1). The particle size of the first filler (B1) is a median size measured by a laser diffraction / scattering method, and the particle size of the second filler (B2) is a value calculated from the BET specific surface area of ​​the second filler (B2).

[0036] As described above, the ratio of the first filler (B1) to the total solid content is 50% by volume or more and 90% by volume or less, and the ratio of the second filler (B2) is 0.1% by volume or more and 2.0% by volume or less. Therefore, the resin composition is likely to have good moldability. That is, when the ratio of the first filler (B1) is 50% by volume or more, the thermal conductivity and heat resistance of the resin composition can be improved, and when it is 90% by volume or less, molding defects of the insulating layer can be prevented. In addition, when the ratio of the second filler (B2) is 0.1% by volume or more, appropriate fluidity can be imparted to the resin composition, and when it is 2.0% by volume or less, molding defects of the insulating layer can be prevented.

[0037] The proportion of the first filler (B1) is more preferably 60% by volume or more, and even more preferably 65% ​​by volume or more. The proportion of the first filler (B1) is more preferably 87% by volume or less, and even more preferably 85% by volume or less. The proportion of the second filler (B2) is more preferably 0.2% by volume or more, and even more preferably 0.3% by volume or more. The proportion of the second filler (B2) is more preferably 1.7% by volume or less, and even more preferably 1.5% by volume or less.

[0038] It is also preferable that the ratio of the second filler (B2) to the solid content excluding the inorganic filler (B) is 1.0 volume % or more and 8.0 volume % or less. In this case, the insulating layer is more easily filled into the gaps in the conductor wiring, and the resin composition is more unlikely to flow out of the insulating layer. That is, when the ratio of the second filler (B2) is 1.0 volume % or more, the resin composition can be given an appropriate fluidity, and when it is 8.0 volume % or less, molding defects of the insulating layer can be less likely to occur. It is more preferable that the ratio of the second filler (B2) is 1.1 volume % or more, and even more preferable that it is 1.2 volume % or more. In addition, it is more preferable that the ratio of the second filler (B2) is 7.0 volume % or less, and even more preferable that it is 5.0 volume % or less.

[0039] The first filler (B1) contains, for example, anhydrous magnesium carbonate filler (b1) and alumina filler (b2). In this case, the anhydrous magnesium carbonate filler (b1) has high heat resistance because it does not have crystallization water. The alumina filler (b2) has even higher heat resistance than the anhydrous magnesium carbonate filler (b1). Therefore, when the first filler (B1) contains the anhydrous magnesium carbonate filler (b1) and the alumina filler (b2), heat resistance can be imparted to the resin composition.

[0040] The particle shape of the anhydrous magnesium carbonate filler (b1) is, for example, polyhedral, but is preferably rounded. Anhydrous magnesium carbonate does not have water of crystallization, and therefore has superior thermal stability compared to the dihydrate, trihydrate, and pentahydrate of anhydrous magnesium carbonate. Therefore, when the first filler (B1) contains the anhydrous magnesium carbonate filler (b1), the heat resistance of the resin composition is likely to be improved. In order to further improve the heat resistance of the resin composition, it is preferable that the first filler (B1) does not contain magnesium carbonate hydrate, or that the magnesium carbonate hydrate in the first filler (B1) is only a trace amount of impurity inevitably mixed in.

[0041] The anhydrous magnesium carbonate filler (b1) has a relatively high thermal conductivity as an inorganic substance, and therefore can improve the thermal conductivity of the resin composition.

[0042] In addition, the anhydrous magnesium carbonate filler (b1) is a crystal having a relatively low Mohs hardness, and therefore when an insulating layer made of a resin composition is processed with a drill, the drill is less likely to be worn down. In other words, the anhydrous magnesium carbonate filler (b1) easily improves the drilling processability of the insulating layer.

[0043] Preferably, the median diameter of the anhydrous magnesium carbonate filler (b1) measured by a laser diffraction / scattering method is 8 μm or more and 30 μm or less. When the median diameter is 8 μm or more, the contact area between the anhydrous magnesium carbonate filler (b1) and the thermosetting resin (A) is reduced, and the thermal conductivity of the cured product of the resin composition is less likely to decrease. When the median diameter is 30 μm or less, the electrical insulation of the cured product of the resin composition is less likely to decrease. The median diameter of the anhydrous magnesium carbonate filler (b1) is more preferably 8 μm or more and 25 μm or less, and even more preferably 8 μm or more and 20 μm or less.

[0044] The alumina filler (b2) has higher thermal conductivity and heat resistance than the anhydrous magnesium carbonate filler (b1), and can therefore further improve the thermal conductivity and heat resistance of the cured product of the resin composition.

[0045] Preferably, the shape of the particles of the alumina filler (b2) is rounded. The rounded shape means a shape that does not have any sharp protruding parts. For example, the rounded shape includes a spherical shape and a spheroidal shape, but does not include a plate shape, a polyhedral shape, a rectangular parallelepiped shape, a rod shape, a needle shape, and a scale shape. When the particles constituting the alumina filler (b2) are rounded, the fluidity of the resin composition during molding is likely to be improved, and therefore the moldability of the resin composition is likely to be improved.

[0046] Since the Mohs hardness of the alumina filler (b2) is relatively high, the smaller the median diameter of the alumina filler (b2) is, the more preferable. Specifically, the median diameter of the alumina filler (b2) is preferably 0.1 μm or more and 5 μm or less. In this case, when the cured product of the resin composition is processed with a drill, the drill is less likely to wear. The median diameter of the alumina filler (b2) is more preferably 0.1 μm or more and 4.0 μm or less, and even more preferably 0.1 μm or more and 3.0 μm or less.

[0047] The ratio of the anhydrous magnesium carbonate filler (b1) is preferably 25% by volume or more and 75% by volume or less with respect to the inorganic filler (B). When the ratio of the anhydrous magnesium carbonate filler (b1) is less than 35% by volume, the ratio of the alumina filler (b2) becomes relatively high. Since the alumina filler (b2) has high hardness, when the ratio of the alumina filler (b2) becomes high, the drilling processability tends to decrease. When the ratio of the anhydrous magnesium carbonate filler (b1) exceeds 65% by volume, the ratio of the alumina filler (b2) becomes relatively low. If the shape (particle shape) of the anhydrous magnesium carbonate filler (b1) is not rounded (e.g., polyhedral), when the content of the anhydrous magnesium carbonate filler (b1) is high, the moldability of the resin composition tends to decrease even if the shape (particle shape) of the alumina filler (b2) is rounded. The proportion of the anhydrous magnesium carbonate filler (b1) is more preferably from 30 vol % to 70 vol % and even more preferably from 35 vol % to 65 vol %.

[0048] The proportion of the alumina filler (b2) relative to the inorganic filler (B) is preferably 25 vol% or more and 75 vol% or less, more preferably 30 vol% or more and 70 vol% or less, and even more preferably 35 vol% or more and 65 vol% or less.

[0049] Preferably, the median diameter of the anhydrous magnesium carbonate filler (b1) is larger than the median diameter of the alumina filler (b2). In this case, the first filler (B1) is likely to be densely packed in the resin composition and its cured product. Then, the particles of the anhydrous magnesium carbonate filler (b1) and the alumina filler (b2) are likely to be close to each other and form a heat conduction path, so that the thermal conductivity of the resin composition and its cured product is likely to be improved. Particularly preferably, as described above, the median diameter of the anhydrous magnesium carbonate filler (b1) is 8 μm or more and 30 μm or less, and the median diameter of the alumina filler (b2) is 5 μm or less. In this case, the thermal conductivity is likely to be further improved.

[0050] The first filler (B1) may further contain components other than the anhydrous magnesium carbonate filler (b1) and the alumina filler (b2). For example, the first filler (B1) may further contain an inorganic filler (b3) carrying a molybdenum compound. The particles of the inorganic filler (b3) have, for example, an inorganic core and a molybdenum compound carried on the core. For example, in the particles of the inorganic filler (b3), a part or all of the surface of the core is covered with a molybdenum compound.

[0051] The inorganic substance in the inorganic filler (b3) is not particularly limited. The inorganic substance contains at least one selected from the group consisting of, for example, carbonates, metal oxides, silicates, and metal hydroxides. The carbonates contain, for example, calcium carbonate. The metal oxides contain, for example, zinc oxide. The silicates contain, for example, talc. The metal hydroxides contain, for example, magnesium hydroxide.

[0052] The molybdenum compound is not particularly limited. The molybdenum compound contains at least one selected from the group consisting of, for example, zinc molybdate, calcium molybdate, magnesium molybdate, molybdenum trioxide, ammonium molybdate, barium molybdate, sodium molybdate, potassium molybdate, phosphomolybdic acid, ammonium phosphomolybdate, sodium phosphomolybdate, silicomolybdic acid, molybdenum boride, molybdenum disilicide, molybdenum nitride, and molybdenum carbide. From the viewpoint of chemical stability, moisture resistance, and insulation, it is preferable that the molybdenum compound contains at least one selected from the group consisting of zinc molybdate, calcium molybdate, and magnesium molybdate.

[0053] When the first filler (B1) contains an inorganic filler (b3), the molybdenum compound is supported on the inorganic core of the inorganic filler (b3), so that the drilling processability of the cured product of the resin composition is further improved. In particular, when the core of the inorganic filler (b3) is talc, the drilling processability is further improved.

[0054] When the first filler (B1) further contains an inorganic filler (b3), the ratio of the inorganic filler (b3) is preferably 10% by volume or less relative to the inorganic filler (B). The inorganic filler (b3) may have lower heat resistance than the anhydrous magnesium carbonate filler (b1) and the alumina filler (b2). Therefore, by making the ratio of the inorganic filler (b3) 10% by volume or less, it is possible to suppress a decrease in the heat resistance of the resin composition.

[0055] The first filler (B1) is preferably surface-treated with a coupling agent. In this case, the adhesion between the thermosetting resin (A) and the first filler (B1) can be improved. The surface treatment method may be a wet treatment method or a dry treatment method. It is also preferable that at least one of the anhydrous magnesium carbonate filler (b1) and the alumina filler (b2) is surface-treated with a coupling agent.

[0056] The coupling agent is not particularly limited as long as it has a reactive group that chemically bonds with an inorganic material and a reactive group that chemically bonds with an organic material in one molecule. Specific examples of the reactive group that chemically bonds with an inorganic material include an ethoxy group and a methoxy group. Specific examples of the reactive group that chemically bonds with an organic material include an epoxy group, an amino group, an isocyanate group, a hydroxy group, a phenolic hydroxy group, and an acid anhydride group.

[0057] The coupling agent includes a silane coupling agent. The silane coupling agent includes, for example, epoxy silane, amino silane, isocyanate silane, and acid anhydride silane. Specific examples of epoxy silane include 3-glycidoxypropyl trimethoxy silane and 3-glycidoxypropyl triethoxy silane. Specific examples of amino silane include 3-aminopropyl triethoxy silane. Specific examples of isocyanate silane include 3-isocyanate propyl triethoxy silane.

[0058] On the other hand, the particle size of the second filler (B2) is nano-sized as described above, and is smaller than the particle size of the first filler (B1). Therefore, the second filler (B2) has a larger specific surface area than the first filler (B1), and can impart appropriate fluidity to the resin composition. The particle size of the second filler (B2) is preferably less than 100 nm, and more preferably 50 nm or less. In this case, an appropriate fluidity can be imparted to the resin composition with a smaller amount. In addition, the specific surface area of ​​the second filler (B2) measured by the BET method is 100 m 2 / g or more 400m 2 / g or less. 2 / g or more, the resin composition can be given an appropriate fluidity, and 2 By keeping the specific surface area at 130 m / g or less, molding defects in the insulating layer can be prevented. 2 / g or more 350m 2 / g or less is preferable, and 150m 2 / g or more 300m 2 It is more preferable that the ratio is 1 / g or less.

[0059] The material of the second filler (B2) is not particularly limited. The second filler (B2) preferably contains at least one of silica and alumina. The silica contains at least one of dry silica such as fumed silica and wet silica produced by a wet method such as a sol-gel method, and the alumina contains dry alumina such as fumed alumina.

[0060] The second filler (B2) is preferably subjected to a hydrophobization treatment. In particular, the second filler (B2) is preferably treated with at least one surface treatment agent selected from the group consisting of alkylsilane, silicone oil, epoxysilane, aminosilane, isocyanatesilane, and acid anhydride silane. In this case, the second filler (B2) is easily dispersed in the resin composition even if it has a small particle size, and therefore does not easily inhibit the flowability of the resin composition.

[0061] The resin composition may further contain additives other than those described above. The additives include at least one selected from the group consisting of, for example, a flame retardant, a coupling agent, and a dispersant. The flame retardant may be an organic flame retardant or an inorganic flame retardant. The organic flame retardant contains at least one selected from the group consisting of, for example, a halogen compound and a phosphorus compound. The phosphorus compound contains at least one selected from, for example, a phosphate ester flame retardant, a phosphazene flame retardant, a bisdiphenylphosphine oxide flame retardant, and a phosphinate flame retardant. The phosphate ester flame retardant contains, for example, a condensed phosphate ester of dixylenyl phosphate. The phosphazene flame retardant contains, for example, phenoxyphosphazene. The bisdiphenylphosphine oxide flame retardant contains, for example, xylylene bisdiphenylphosphine oxide. The phosphinate flame retardant contains, for example, a metal phosphinate salt of aluminum dialkylphosphinate. The inorganic flame retardant contains, for example, a metal hydroxide.

[0062] The coupling agent is not particularly limited as long as it has a reactive group that chemically bonds with an inorganic material and a reactive group that chemically bonds with an organic material in one molecule. Specific examples of the reactive group that chemically bonds with an inorganic material include an ethoxy group and a methoxy group. Specific examples of the reactive group that chemically bonds with an organic material include an epoxy group, an amino group, an isocyanate group, a hydroxy group, a phenolic hydroxy group, and an acid anhydride group. The coupling agent includes a silane coupling agent. The silane coupling agent includes, for example, an epoxy silane, an amino silane, an isocyanate silane, and an acid anhydride silane. Specific examples of the epoxy silane include 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane. Specific examples of the amino silane include 3-aminopropyltriethoxysilane. Specific examples of the isocyanate silane include 3-isocyanatepropyltriethoxysilane. When the resin composition further contains a coupling agent, the adhesion between the organic material and the inorganic material can be improved.

[0063] The dispersant is a type of surfactant and is not particularly limited. When the resin composition further contains a dispersant, the dispersibility of the first filler (B1) and the second filler (B2) tends to be improved.

[0064] The resin composition can be prepared by mixing the above components. When the thermosetting resin (A) is solid at room temperature, it is preferable that the resin composition further contains a solvent. The solvent is not particularly limited as long as it can dissolve at least the thermosetting resin (A), and an example of the solvent is methyl ethyl ketone. When the thermosetting resin (A) is liquid at room temperature, it is not necessary to further contain a solvent.

[0065] The resin film 1 according to this embodiment includes a resin composition, a dried product of the resin composition, or a semi-cured product of the resin composition. The resin film 1 is produced, for example, by applying the resin composition to a support film and then heating the resin composition. The resin film 1 is used after being peeled off from the support film. The support film is, for example, a polyethylene terephthalate (PET) film.

[0066] By curing the resin film 1, for example, the insulating layer 40 of the metal-clad laminate 4 and the insulating layer 50 of the printed wiring board 5 can be produced.

[0067] The thickness of the resin film 1 is, for example, not less than 50 μm and not more than 200 μm, but is not limited to this.

[0068] The resin-coated metal foil 2 according to this embodiment includes a resin layer 20 and a metal foil 21 overlapping the resin layer 20. The resin layer 20 contains a resin composition, a dried product of the resin composition, or a semi-cured product of the resin composition.

[0069] The resin-coated metal foil 2 is produced, for example, by applying a resin composition to the metal foil 21 and then heating the resin composition to form the resin layer 20.

[0070] By curing the resin layer 20 of the resin-coated metal foil 2, for example, the insulating layer 40 of the metal-clad laminate 4 and the insulating layer 50 of the printed wiring board 5 can be produced.

[0071] The prepreg 3 according to this embodiment includes a substrate, and a resin composition impregnated in the substrate, a dried product of the resin composition, or a semi-cured product of the resin composition.

[0072] The prepreg 3 is produced, for example, by impregnating a base material 31 with a resin composition and then heating the impregnated base material 31. The base material 31 is, for example, a glass cloth.

[0073] By curing the prepreg 3, for example, the insulating layer 40 of the metal-clad laminate 4 and the insulating layer 50 of the printed wiring board 5 can be produced.

[0074] 4, the metal-clad laminate 4 according to this embodiment includes an insulating layer 40 and a metal foil 41. The insulating layer 40 includes a cured product of a resin composition. The metal foil 41 is adhered to the insulating layer 40.

[0075] The metal foil 41 is, for example, a copper foil. The thickness of the metal foil 41 is not particularly limited, but is preferably 12 μm or more and 420 μm or less, and more preferably 18 μm or more and 210 μm or less. The ten-point mean roughness Rzjis of the metal foil 41 is also not particularly limited, but is preferably 3 μm or more, and more preferably 5 μm or more. If the ten-point mean roughness Rzjis of the metal foil 41 is 3 μm or more, the adhesion between the insulating layer 40 and the metal foil 41 can be further improved.

[0076] The metal-clad laminate 4 can be produced, for example, by hot pressing a laminate obtained by laminating one prepreg 3 or two or more prepregs 3, and then laminating a metal foil 41 on one or both sides of the laminate. Preferably, before laminating the metal foil 41 on the prepreg 3, the surface of the metal foil 41 (at least the surface that overlaps the prepreg 3) is treated with a coupling agent. When the metal foil 41 is surface-treated with a coupling agent, the coupling agent bonds the organic material in the prepreg 3 with the metal foil 41, thereby further improving the adhesion between the insulating layer 40 and the metal foil 41. The coupling agent can be one described above. The conditions of the heat press are not particularly limited. FIG. 4 shows a metal-clad laminate 4 having two substrates 31 in the insulating layer 40. In this embodiment, the resin composition has an appropriate fluidity, so that the resin composition, the dried product of the resin composition, or the semi-cured product of the resin composition is unlikely to flow out of the prepreg produced from the resin composition when the laminate is hot pressed. For this reason, molding defects are unlikely to occur.

[0077] As shown in FIG. 5A and FIG. 5B, the printed wiring board 5 according to the present embodiment includes an insulating layer 50 and a conductor layer 51. The insulating layer 50 includes a cured product of a resin composition. The conductor layer 51 is bonded to the insulating layer 50. The conductor layer 51 refers to a conductive layer such as a signal layer, a power layer, and a ground layer. The conductor layer 51 may be a conductor wiring or a metal foil without a pattern. The printed wiring board 5 is a concept including a multilayer printed wiring board having three or more conductor layers 51. In particular, FIG. 5B shows a multilayer printed wiring board 5 having three conductor layers 51.

[0078] The printed wiring board 5 can be manufactured, for example, by using a subtractive method with the above-mentioned metal-clad laminate 4 as a material. The printed wiring board 5 may also be multi-layered using a build-up method.

[0079] Specifically, for example, a conductor wiring is produced as a conductor layer 51 from the metal foil 41 of the metal-clad laminate 4 by a subtractive method or the like, thereby manufacturing the printed wiring board 5 shown in FIG. 5A. A via may be produced by processing the metal-clad laminate 4 with a drill to produce a hole, and plating the inner surface of the hole during the production of the conductor wiring. That is, a printed wiring board 5 having a via may be produced. In this case, in this embodiment, the drill is less likely to wear out.

[0080] The printed wiring board 5 can also be manufactured as follows. A conductor wiring is prepared as the conductor layer 51 from the metal foil 41 of the metal-clad laminate 4 by a subtractive method or the like to prepare a core material 6. That is, the printed wiring board 5 shown in FIG. 5A is the core material 6. This core material 6 and the metal foil 2 with resin are laminated so that the resin layer 20 of the metal foil 2 with resin overlaps one conductor wiring of the core material 6. In this state, the core material 6 and the metal foil 2 with resin are heat-pressed. At this time, in this embodiment, the resin composition has an appropriate fluidity, so that the resin composition, the dried product of the resin composition, or the semi-cured product of the resin composition does not easily flow out from the resin layer 20 prepared from the resin composition. In addition, the resin layer 20 easily flows into the gaps of the conductor wiring. The insulating layer 22 is prepared by curing this resin layer 20, and at this time, the insulating layer 22 is easily filled sufficiently into the gaps of the conductor wiring. Then, a conductor wiring, which is a conductor layer 51, can be produced from the metal foil 21 derived from the resin-coated metal foil 2 by a subtractive method or the like. As a result, as shown in FIG. 5B, a multilayer printed wiring board 5 can be produced. This multilayer printed wiring board 5 includes, as an insulating layer 50, an insulating layer 40 derived from the core material 6 and an insulating layer 22 produced from the resin layer 20 of the resin-coated metal foil 2. In addition, by using this multilayer printed wiring board 5 as a core material and using the resin-coated metal foil 2 in the same manner as above, a further multilayer printed wiring board 5 can be produced. This printed wiring board 5 can be processed with a drill to form a hole, and the inner surface of this hole can be plated to produce a via. In this case, the drill is less likely to wear in this embodiment.

[0081] The printed wiring board 5 can also be manufactured as follows. The core material 6, the resin film 1, and the metal foil are laminated so that the resin film 1 overlaps the conductor wiring of the core material 6, and the metal foil overlaps on the resin film 1. In this state, the core material 6, the resin film 1, and the metal foil are heat-pressed. At this time, in this embodiment, the resin composition has an appropriate fluidity, so that the resin composition, the dried product of the resin composition, or the semi-cured product of the resin composition does not easily flow out from the resin film 1 made from the resin composition. In addition, the resin film 1 easily flows into the gaps of the conductor wiring. An insulating layer is produced by curing this resin film 1, and at this time, the insulating layer is likely to be sufficiently filled in the gaps of the conductor wiring. Subsequently, the conductor wiring can be produced from the metal foil by a subtractive method or the like. This allows the multilayer printed wiring board 5 to be manufactured. In addition, by using this multilayer printed wiring board 5 as a core material and using a metal foil with resin in the same manner as described above, a further multilayer printed wiring board 5 can be manufactured. A via can also be fabricated by drilling this printed wiring board 5 to form a hole and plating the inner surface of the hole. In this case, in this embodiment, the drill is less likely to wear out.

[0082] In the above explanation, the core material 6 is made from a metal-clad laminate 4 having an insulating layer 40 made from the resin composition of this embodiment, and the printed wiring board 5 is manufactured from this core material 6, but the core material 6 is not limited to the above, that is, the insulating layer 40 in the core material 6 does not have to be made from the resin composition of this embodiment. EXAMPLES

[0083] Specific examples of the present embodiment will be presented below. Note that the present embodiment is not limited to the following examples.

[0084] 1.Raw materials The following raw materials were prepared: -Epoxy resin 1: Manufactured by DIC Corporation. Naphthalene type liquid epoxy resin. Product name HP-4032D. Specific gravity 1.20. Liquid at room temperature. -Epoxy resin 2: Manufactured by DIC Corporation. Naphthalene type epoxy resin. Product name HP-4710. Specific gravity 1.20. Softening point 95°C. -Epoxy resin 3: Bisphenol A type epoxy resin. Manufactured by DIC Corporation. Product name: Epicron 850-S. Specific gravity: 1.15. Liquid at room temperature. -Epoxy resin 4:3 functional epoxy resin. Printec Co., Ltd. Product name VG-3101. Specific gravity 1.18. Softening point 61°C. -Phenoxy resin: Manufactured by Nippon Steel Chemical & Material Co., Ltd. Product name: YP-50. -Polyphenylene ether resin: SABIC Japan. Product name: SA-90. -Phenol resin 1: Phosphorus-containing phenol resin. Manufactured by The Dow Chemical Company. Product name: XZ92741. -Phenol resin 2: Manufactured by Meiwa Kasei Co., Ltd. Product name: MEH-7600-4H. -Hardening agent: Dicyandiamide. - Catalyst: 2-ethyl-4-methylimidazole. -Flame retardant: Daihachi Chemical Industry Co., Ltd. Phosphate ester. Product name: PX-200. Specific gravity: 1.26. -Coupling agent: Shin-Etsu Chemical Co., Ltd. Silane coupling agent. Product name: KBE-403. Specific gravity: 1.00. -Dispersant: BYK Japan Co., Ltd. Wetting dispersant. Product name: BYK-W903. Specific gravity: 1.00. -Leveling agent: DIC Corporation. Product name: F-556. Specific gravity: 1.00. -Anhydrous magnesium carbonate filler: manufactured by Konoshima Chemical Co., Ltd. Synthetic magnesite. Product name: MS-PS. Median diameter: 12 μm. Specific gravity: 3.04. -Alumina filler: Admatechs Co., Ltd. Spherical alumina. Product name: AO-502. Median diameter: 0.25 μm. Specific gravity: 3.96. -Talc: Manufactured by Huber. Calcium carbonate supported with calcium molybdate. Product name: KG-501. Median diameter: 4.5 μm. Specific gravity: 3.00. - Dry silica 1: Evonik. Fumed silica. Product name: Aerosil R972. BET specific surface area: 110 m 2 / g. Specific gravity 2.20. - Fumed silica 2: Evonik. Fumed silica. Product name: Aerosil R974. BET specific surface area: 170 m 2 / g. Specific gravity 2.20. - Fumed silica 3: Evonik. Fumed silica. Product name: Aerosil R976S. BET specific surface area: 240 m 2 / g. Specific gravity 2.20. - Dry silica 4: Evonik. Fumed silica. Product name: Aerosil RX200R. BET specific surface area: 140m 2 / g. Specific gravity 2.20. - Fumed silica 5: Evonik. Fumed silica. Product name: Aerosil RX300. BET specific surface area: 210 m 2 / g. Specific gravity 2.20. - Fumed silica 6: Evonik. Fumed silica. Product name: Aerosil R805. BET specific surface area: 150 m 2 / g. Specific gravity 2.20. -Dry alumina: Evonik. Fumed alumina. Product name: Aeroxide AluC805. BET specific surface area: 90m 2 / g. Specific gravity 3.96. -Wet silica 1: Nissan Chemical Co., Ltd. Methyl ethyl ketone dispersed silica sol. Product name: MEK-EC-2130Y. BET specific surface area: 230 m 2 / g. Specific gravity 2.20. -Wet silica 2: Nissan Chemical Co., Ltd. Methyl ethyl ketone dispersed silica sol. Product name: MEK-EC-2430Z. BET specific surface area: 230 m 2 / g. Specific gravity 2.20.

[0085] Each of the dry silica, dry alumina, and wet silica is surface-treated with at least one surface treatment agent selected from alkylsilane, silicone oil, and epoxysilane. As for the surface treatment method, in the case of dry fillers (dry silica and dry alumina), a method of hydrophobizing in a fluidized bed using organohalogen silane or a method of hydrophobizing organopolysiloxane using an alkali catalyst is used. In the case of wet silica, a method of hydrophobizing is used in which a mixture containing a silylating agent, a hydrophobic organic solvent, an alcohol, and water is added to hydrophilic colloidal silica, and the mixture is aged at 0°C to 100°C in a state in which the alkali has been removed or neutralized with an equivalent or more amount of acid.

[0086] 2. Preparation of the Composition The above raw materials were mixed according to the compositions shown in Tables 1 to 3, and then methyl ethyl ketone and dimethylformamide were added so that the solid concentration was 80 to 95 mass %, and the mixture was stirred with a planetary mixer to prepare a composition.

[0087] 3. Preparation of resin film The composition was applied onto a polyethylene terephthalate film and then heated at about 150° C. for 3 to 5 minutes to semi-cure the resin composition, thereby producing a resin film with a thickness of 100 μm.

[0088] 4.Evaluation Test (1) Film properties The appearance of the resin film was checked when it was wrapped around a SUS rod having a diameter of 10 mm and when it was wrapped around a SUS rod having a diameter of 100 mm.

[0089] As a result, the resin film was rated as "A" when no cracks were found in the resin film when it was wrapped around either rod, as "B" when cracks were found in the resin film only when it was wrapped around a 10 mm diameter SUS rod, and as "C" when cracks were found in the resin film when it was wrapped around either rod.

[0090] (2) Resin flow The resin film was cut to a size of 100 mm x 100 mm in plan view to prepare a test sample. Two of these samples were stacked and the weight was measured.

[0091] The release-treated surfaces of the polyethylene terephthalate films were placed facing each other, and two overlapping samples were placed between them. In this state, the sample and the polyethylene terephthalate film were heat-pressed at 130°C, 5 minutes, and 0.5 MPa (condition 1) to produce a cured product from the sample. The cured product was punched out with a mold to produce a post-treatment sample with a plan view of 80 mmΦ, and its weight was measured. The resin flow was calculated from the weight of the sample M0 and the weight of the post-treatment sample M using the following formula. Resin flow (%) = (M0-2M) / M0 x 100 The resin flow was also calculated in the same manner when the heat press was performed under conditions of 130° C., 5 minutes, and 2.0 MPa (condition 2).

[0092] The resin flow rate was evaluated as "A" when the resin flow rate under condition 1 was 30% or less and the resin flow rate under condition 2 was more than 45%. The resin flow rate under condition 1 was more than 30% and the resin flow rate under condition 2 was more than 45%. The resin flow rate under condition 1 was evaluated as "B". The resin flow rate under condition 1 was evaluated as 30% or less and the resin flow rate under condition 2 was evaluated as 45% or less.

[0093] (3) Fillability A double-sided copper-clad laminate (manufactured by Panasonic Corporation, product number R-1566, copper foil 35 μm) was prepared. The copper foil of this double-sided copper-clad laminate was etched to produce a grid-shaped conductor wiring, and a printed wiring board for testing was obtained. A resin film was placed on each of the two conductor wirings in the printed wiring board, and the board was heated at 200° C. and 2.94 MPa (30 kgf / cm 2 The laminate was fabricated by heat pressing under the conditions of 20%, 50%, and 80% residual copper ratio of the conductor wiring.

[0094] The presence or absence of voids inside the insulating layer made of the resin film in the laminate was visually inspected, and the case where no voids were found was rated as "A", and the case where voids were found was rated as "B".

[0095] (4) Thermal conductivity Eight sheets of 100 μm thick resin film were laminated, sandwiched between the roughened surfaces of two sheets of copper foil (thickness 35 μm), and heated at 195°C and 2.94 MPa (30 kgf / cm 2 ) for 60 minutes to produce a copper-clad laminate (CCL) with a total insulating layer thickness of 800 μm.

[0096] The copper foil of the copper-clad laminate was removed by etching to obtain a resin plate, and the thermal diffusivity α of the plate was evaluated by the laser flash method, the specific heat Cp by the DSC method, and the specific gravity ρ by the water substitution method. From these results, the thermal conductivity λ was calculated using the following formula.

[0097] λ(W / m K)=α(m 2 / s) × Cp (J / kg K) × ρ (kg / m 3 ) The test results are shown in Tables 1 to 4.

[0098] [Table 1]

[0099] [Table 2]

[0100] [Table 3]

[0101] [Table 4] [Explanation of symbols]

[0102] 1 Resin film 2. Metal foil with resin 20 Resin layer 21 Metal foil 3 Prepreg 31 Base material 4 Metal-clad laminate 40 Insulating layer 41 Metal foil 5. Printed Wiring Boards 50 Insulating layer 51 Conductor layer

Claims

1. A resin composition containing a thermosetting resin (A) and an inorganic filler (B), The inorganic filler (B) contains a first filler (B1) and a nano-sized second filler (B2) having a particle size smaller than that of the first filler (B1), the particle size of the first filler (B1) is a median size determined by a laser diffraction / scattering method, and the particle size of the second filler (B2) is a value calculated from the BET specific surface area of ​​the second filler (B2); The first filler (B1) contains anhydrous magnesium carbonate filler (b1) and an alumina filler (b2), a ratio of the first filler (B1) to a total solid content in the resin composition is 50 vol% or more and 90 vol% or less, and a ratio of the second filler (B2) to a total solid content in the resin composition is 0.1 vol% or more and 2.0 vol% or less, The ratio of the alumina filler (b2) to the inorganic filler (B) is 25% by volume or more and 75% by volume or less. Resin composition.

2. The ratio of the second filler (B2) to the solid content excluding the inorganic filler (B) is 1.0 vol% or more and 8.0 vol% or less. The resin composition according to claim 1.

3. The ratio of the anhydrous magnesium carbonate filler (b1) to the inorganic filler (B) is 25% by volume or more and 75% by volume or less. The resin composition according to claim 1 or 2.

4. The anhydrous magnesium carbonate filler (b1) has a median diameter of 8 μm or more and 30 μm or less, as measured by a laser diffraction / scattering method; The alumina filler (b2) has a median diameter of 0.1 μm or more and 5 μm or less, as measured by a laser diffraction / scattering method. The resin composition according to claim 1 .

5. The second filler (B2) has a specific surface area of ​​100 m2 measured by the BET method. 2 / g or more 400m 2 / g or less, The resin composition according to any one of claims 1 to 4.

6. The second filler (B2) is treated with at least one surface treatment agent selected from the group consisting of alkylsilane, silicone oil, epoxysilane, aminosilane, isocyanate silane, and acid anhydride silane. The resin composition according to any one of claims 1 to 5.

7. The thermosetting resin (A) contains an epoxy resin (a), The epoxy resin (a) contains an epoxy resin (a1) having a softening point of 75° C. or lower in an amount of 30% by mass or more based on the epoxy resin (a). The resin composition according to any one of claims 1 to 6.

8. The resin composition according to any one of claims 1 to 7, a dried product of the resin composition, or a semi-cured product of the resin composition, Resin film.

9. A resin layer containing the resin composition according to any one of claims 1 to 7, a dried product of the resin composition, or a semi-cured product of the resin composition; A metal foil overlying the resin layer. Metal foil with resin.

10. A substrate; The resin composition according to any one of claims 1 to 7, which is impregnated into the substrate, a dried product of the resin composition, or a semi-cured product of the resin composition, Prepreg.

11. An insulating layer containing a cured product of the resin composition according to any one of claims 1 to 7; and a metal foil overlying the insulating layer. Metal-clad laminate.

12. An insulating layer containing a cured product of the resin composition according to any one of claims 1 to 7; a conductor layer overlying the insulating layer, Printed wiring board.

Citation Information

Patent Citations

  • Heat-conductive resin composition, resin sheet, prepreg, metal laminated plate, and print wiring board

    JP2012087250A

  • Resin composition, resin sheet, prepreg, laminated board, metal substrate, and printed wiring board

    JP2012211225A

  • Insulating sheet and multilayer structure

    WO2010016480A1